The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1029/2020gl088540
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Properties of Magnetic Structures and Energy Dissipation during Turbulent Reconnection in the Earth's Magnetotail

Abstract: We present the first statistical study of magnetic structures and associated energy dissipation observed during a single period of turbulent magnetic reconnection, by using the in situ measurements of the Magnetospheric Multiscale mission in the Earth's magnetotail on 26 July 2017. The structures are selected by identifying a bipolar signature in the magnetic field and categorized as plasmoids or current sheets via an automated algorithm which examines current density and plasma flow. The size of the plasmoids… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…(2013). On the other hand, one can also find the observation results which have a similar energy conversion allocation between parallel and perpendicular parts (e.g., Bergstedt et al., 2020).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…(2013). On the other hand, one can also find the observation results which have a similar energy conversion allocation between parallel and perpendicular parts (e.g., Bergstedt et al., 2020).…”
Section: Resultsmentioning
confidence: 75%
“…Assisted with our simulation which uses higher grid resolution, the perpendicular dominant pressure anisotropy within the inner EDR can be revealed more distinctively than the results shown in Figure 12a of Egedal et al (2013). On the other hand, one can also find the observation results which have a similar energy conversion allocation between parallel and perpendicular parts (e.g., Bergstedt et al, 2020).…”
Section: Parallel Energy Versus Perpendicular Energymentioning
confidence: 61%
“…The most probable Wnormalcnormalhnormalanormalonormaltnormalinormalc ${W}_{\mathrm{c}\mathrm{h}\mathrm{a}\mathrm{o}\mathrm{t}\mathrm{i}\mathrm{c}}$ was as high as 3 MeV. This is because the strong helical magnetic field lines in the flux ropes correspond to large curvature radii of the magnetic field lines (e.g., Bergstedt et al., 2020; Shen et al., 2007; Sun et al., 2019; Y. C. Zhang et al., 2013), which in turn results in high Wnormalcnormalhnormalanormalonormaltnormalinormalc ${W}_{\mathrm{c}\mathrm{h}\mathrm{a}\mathrm{o}\mathrm{t}\mathrm{i}\mathrm{c}}$. The electrons in the energy range from ∼50 to 200 keV investigated here were in regular orbit inside the flux ropes.…”
Section: Energization Of Electrons Associated With Flux Ropes and X‐l...mentioning
confidence: 99%
“…These observations might indicate that the magnetic field and plasma process are turbulent during this interval around the flux rope, which might be driven by the frequently appearing reconnection X-lines surrounding the flux rope pair. In the turbulent plasma sheet, as shown in Bergstedt et al (2020) and Ergun et al (2020a), significant electromagnetic field energy is observed to be converted to particles, however, a large fraction of energy can return from particles to the electromagnetic field.…”
Section: Energization Mechanisms In Flux Ropes and Between Flux Ropesmentioning
confidence: 99%
“…Observationally, there is ample direct in-situ evidence for the existence of multiple X-line regime in Earth's magnetosphere [101][102][103] and indirect evidence from remote-sensing solar observations 104,105 . However, the limited statistical studies of these observations as well as from the laboratory (see below) suggest exponential distributions 96,[106][107][108][109][110][111] . It is unclear why this qualitative discrepancy exists, but multi-spacecraft missions with in-situ measurements, such as the current Magnetospheric MultiScale (MMS) mission 32 with many more satellites are required to better observe multiscale reconnection phenomena.…”
Section: Plasmoid-mediated Multiscale Reconnectionmentioning
confidence: 99%